Analysis of Islamic Law and Positive Law in Preventing Unregistered (Siri) Marriages at the Giri Menang Religious Court of West Lombok - Muliadi, Ahmad (MAQASIDI: Jurnal Syariah dan Hukum published by the Islamic Criminal Law Program of the Sharia and Islamic Economics Department at the Sekolah Tinggi Agama Islam Negeri Teungku Dirundeng Meulaboh, 2025)
Unregistered or siri marriages remain a widespread phenomenon across various regions in Indonesia, including West Lombok Regency. This practice is generally driven by cultural and economic factors, as well as the lack of legal awareness among the community. Although such marriages may be considered valid under Islamic law, they lack legal force under positive law due to the absence of official registration. This creates numerous legal issues, particularly concerning the rights of wives and children, and the legal protection of the involved parties. This study aims to analyze how siri marriages occur in West Lombok Regency and to examine the roles of Islamic law and positive law in preventing them, with a specific focus on the role of the Giri Menang Religious Court. The research employs a qualitative method with a descriptive approach, utilizing observation, interviews, and documentation as data collection techniques. The research subjects include judges, court officials, and community members who have experienced or are knowledgeable about siri marriages. The findings reveal that siri marriages are often carried out due to economic reasons and procedural simplicity, alongside the prevailing perception that religious solemnization alone is sufficient without the need for civil registration. The Giri Menang Religious Court plays a crucial role in providing legal education to the public and in handling isbat nikah (marriage validation) cases as a means of legalizing siri marriages. However, challenges persist, particularly in shifting societal paradigms and strengthening the integration between religious norms and state law. Therefore, an integrative approach between Islamic law and positive law is essential in preventing siri marriages, along with reinforcing the institutional roles of religious courts and marriage registration agencies to ensure legal certainty and justice for all citizens.